Mental Health Staff Perspectives on Spiritual Care Competencies in Norway: A Pilot Study - Cone, Pamela; Giske, Tove (Frontiers in Psychology, 2022)
Spirituality and spiritual care have long been kept separate from patient care in mental health, primarily because it has been associated with psycho-pathology. Nursing has provided limited spiritual care competency training for staff in mental health due to fears that psychoses may be activated or exacerbated if religion and spirituality are addressed. However, spirituality is broader than simply religion, including more existential issues such as providing non-judgmental presence, attentive listening, respect, and kindness. Unfortunately, healthcare personnel working in mental health institutions are not well prepared to address spiritual concerns or resources of their patients. Therefore, a mixed-method pilot study was conducted using a self-assessment survey tool to examine spiritual care competencies of mental health staff in Norway and to understand the perspectives of mental health staff in the Scandinavian context. Five questions and comments related to survey items provided rich qualitative data. While only a small pilot with 24 participants, this study revealed a need for spiritual care educational materials targeted specifically for those who work in mental health, materials that address the approach of improving attitudes, enhancing skills, and increasing knowledge related to spirituality and spiritual care of patients.